A comparison of long‐term medium secure patients within NHS and private and charitable sector units in England. (15th March 2020) - Kasmi, Yasir; Duggan, Conor; Völlm, Birgit
Abstract: Background: In England, forensic psychiatric hospital services are provided at three security levels: high, medium and low. All are publicly funded and similarly regulated, but medium and low secure services are provided in the private and charitable (PCS) sector as well as the National Health Service (NHS). Originally, medium secure hospital services were conceived as for up to 2 years' inpatient stay, but numbers of longer stay patients have been rising. Little is known about their characteristics or whether they differ between NHS and PCS settings. Aims: To describe and compare characteristics of long‐stay patients in NHS and in PCS medium security hospital units. Methods: Data were extracted from clinical records in 14 NHS and 9 PCS hospital units for all patients fulfilling criteria for long stay: having been in high security for more than 10 years or medium security for more than 5 years or in a mix of both for more than 15 years in total. Results: 178 NHS and 107 PCS patients were eligible for inclusion, respectively, 16 and 22% of the total patient populations in these settings. The mean length of stay in a medium or high secure setting was similar: 163 and 164 months. Characteristics of the patients, however, differed between unit type. NHS services admitted more patients from prison and PCS services more from other hospitals. NHS services included a lower proportion of patients with personality disorder or intellectual disability. 'Challenging behaviour' was more prevalent in PCS; a history of absconding was found more often among NHS patients. Conclusions: The two systems of service appear to be used differently. More research is needed to explain why patients apparently without behavioural disturbances remain in specialist secure facilities for such a long time and whether their needs are truly being met in the least restrictive environment possible.